Propuesta de tecnificación de 5 ha de pasto Ray Grass (Lolium multiflorum), con riego por aspersión en la zona de Huascazala – distrito de Molinopampa – provincia de Chachapoyas – región Amazonas - Avila Chuquimbalqui, Jessica Elizabeth (2019)
The present thesis entitled "Technification proposal of 5 ha of grass Ray Grass (Lolium multiflorum), with sprinkler irrigation in the zone of _Huascazala - Molinopampa district - Chachapoyas province - Amazonas region", contemplates the design of an irrigation system in 5 ha, which is developed in the annex of Huascazala, District of Molinopampa, Province of Chachapoyas, in the Department of Amazonas, at a height of 2407 meters above sea level which aims to be a productive and sustainable project that allows the farmer to improve their quality of life. The project will benefit 10 families of the annex of Huascazala, with the sprinkler irrigation system, which will improve the increase of agricultural production with a livestock purpose for internal and external consumption of the beneficiaries, will take advantage of the steep slopes of the relief to generate pressure and generate a uniform technical irrigation, allowing us to design pressurized irrigation systems for mountainous areas at a significantly lower cost than on the coast. The source of water comes from Quebrada Colmal according to the hydrological study carried out this source has a maximum flow of 20 l / s, of which we will only use 7.5 l /s for the design of infrastructure, its affluence ensures the provision of water, for the project. So that this sector does not have infrastructure for irrigation, it has been proposed the construction of a catchment and a reservoir with a storage capacity of 648m3. The water collected from the catchment will be transferred to the reservoir with a 4 "pipeline, from which it is then distributed to the irrigation plot with a 4" mm pipeline, which will lead to the valves of the irrigation plots with diameters of 110mm, 90mm and 63mm.